Answer:
The answer is D, (-3,3)
Step-by-step explanation:
Multiply K's cooridinates (-2,2) by 3/2. (-2 × 3/2) (2× 3/2)
When x is equal to -1:
f(-1)=6(-1)-3
=-7-3
=-10
y=-10
When x is equal to 0:
f(0)=6(0)-3
=0-3
=-3
y=-3
When x is equal to 1:
f(1)=6(1)-3
=6-3
=3
y=3
When x is equal to 2:
f(2)=6(2)-3
=12-3
=9
y=9
Answer: -91
Step-by-step explanation:
13x, x=-7
plug in the -7 to x
13(-7)
multiply
<h3>
-91</h3>
Answer:
14
Step-by-step explanation:
Since gaining fourteen pounds means going in a positive direction, we can say the gain of fourteen pounds numerically as 14.